2017
DOI: 10.1097/tp.0000000000001682
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Tranexamic Acid in Orthotopic Liver Transplantation Clinical Practice

Abstract: TXA appears effective in reducing red blood cell transfusion requirements without increasing the risk of thromboembolic events across a wide variety of liver transplant recipients, including those at low risk of bleeding or high risk of thromboembolic complications. We did not detect evidence of an increased risk of thrombotic complications with TXA exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…For this reason, tranexamic acid is often used, either in a prophylactic manner or according to viscoelastic tests. Notably, many studies do not detect thrombotic complications and therefore suggest that tranexamic acid is a safe medication in this setting [ 8 , 15 ]. Two recent studies, however, interpreted their findings on TEG™ clot lysis with mortality as a harmful effect of hypofibrinolysis and fibrinolytic shutdown [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, tranexamic acid is often used, either in a prophylactic manner or according to viscoelastic tests. Notably, many studies do not detect thrombotic complications and therefore suggest that tranexamic acid is a safe medication in this setting [ 8 , 15 ]. Two recent studies, however, interpreted their findings on TEG™ clot lysis with mortality as a harmful effect of hypofibrinolysis and fibrinolytic shutdown [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…42 In a randomized trial, Badenoch et al demonstrated that the efficacy of TXA in reducing blood loss and transfusion requirements during liver transplantation without increasing the risk of thromboembolic events. 43 In literature, RCTs demonstrated approximately (30-40)% reduction in bleeding and need for transfusion requirements during orthotopic liver transplantation as compared to placebo group. 43…”
Section: Efficacy Of Txa In Liver Surgerymentioning
confidence: 99%
“…43 In literature, RCTs demonstrated approximately (30-40)% reduction in bleeding and need for transfusion requirements during orthotopic liver transplantation as compared to placebo group. 43…”
Section: Efficacy Of Txa In Liver Surgerymentioning
confidence: 99%
“…64 Three recent studies demonstrated that prophylactic use of lysine analogs decreased transfusion requirements, although one study showed that antifibrinolytic therapy was associated with a higher risk of deep venous thromboses. [97][98][99] Postoperative Care of the Liver Transplant Recipient…”
Section: Neohepatic Stagementioning
confidence: 99%